Correction of leukocyte adhesion deficiency type II with oral fucose. - Marquardt, T; Lühn, K; Srikrishna, G; Freeze, H; Harms, E; Vestweber, D (1999)
We describe a simple, noninvasive, and effective therapy for leukocyte adhesion deficiency type II (LAD II), a rare inherited disorder of fucose metabolism. This disorder leads to an immunodeficiency caused by the absence of carbohydrate-based selectin ligands on the surface of neutrophils as well as to severe psychomotor and mental retardation. The fucosylation defect in LAD II fibroblasts can be corrected by addition of L-fucose to the culture medium. This prompted us to initiate dietary fucose therapy on a patient with LAD II. Oral supplementation of fucose in this patient induced the expression of fucosylated selectin ligands on neutrophils and core fucosylation of serum glycoproteins. During 9 months of treatment, infections and fever disappeared, elevated neutrophil counts returned to normal, and psychomotor capabilities improved.